Analytical Study of Finite/Infinite Impulse Response Optical Filter for Signal Processing Application (International Journal of Communication Systems and Network Technologies, 2012)
Re-circulating/infinite impulse response (feed-backward) and non-recirculating/finite impulse response (feed-forward) delay line are two structures that are basic to fiber-optic signal processing. Similarly, we can form the re-circulating and nonrecirculating system consists of many more coupler system. In this paper we have analyzed the response of each combination. Later on, we try to connect the z-transform domain into Laplace by replacing z = esT . By replacing the z by the expansion of esT for some number of elements we can obtain the similar types of response to check the validity of our approximations. Here in s-domain we can easily apply control theory concepts on these transfer formulas. In the end we have tried to obtain the time domain response of filter by using the z-domain approximation in s-domain.
Keywords: Signal Processing Concept; Z-transform; S-domain; Optical Directional Coupler